Branded entertainment in Korea - Yoon, Hyunsun (Routledge, 2020)
Branded Entertainment in Korea examines the varied texts and wider context of branded entertainment and related advertising and marketing communications practices in Korea. The book discusses the origins, development, current state, ethics, and regulations of branded entertainment in Korea, considering the impact and implications for communication users and regulators as well as industry actors. Over30 cases from 2013 to 2019 are offered to provide an up-to-date account of current developments, with a closer look at the ethical challenges and controversies surrounding branded entertainment. The book also provides a review of branded entertainment-related literature in order to help the readers to understand this growing marketing discipline. This is a valuable case study for scholars and students of critical advertising studies, as well as those interested in broader disciplines of communication and media studies.- Resumé vydavatel
Keywords: marketingová komunikace -- Korejská republika; masmédia -- Korejská republika; obchodní komunikace -- Korejská republika; obchodní značky -- Korejská republika; zábava; communication in marketing -- Korea (South); mass media -- Korea (South); communication in business -- Korea (South); brand name products -- Korea (South); entertainment; branding (marketing); elektronické knihy; monografie; electronic books; monographs